MENINGKATKAN PEMAHAMAN TENTANG ILMU TAJWID KEPADA ANAK-ANAK DI DESA SUMBERREJO KEC. BATANGHARI KAB. LAMPUNG TIMUR - Hariroh, Nur; Novitasari, Delfi Olvia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
There are many problems, especially in understanding the science of recitation which is the way of the Prophet Muhammad in reading the Qur'an. In this day and age most people do not know about the science of recitation.The results can be self-defeating. In today's life, humans should always give the example of the Prophet Muhammad as an example in reading the Qur'an.The purpose of this activity is to increase understanding of the science of recitation for children in Sumberrejo village,Batanghari sub-district,East Lampung district. Where the science of recitation is very important in reading the Qur'an. The service program carried out is to increase children's understanding of the science of recitation, the priority of the program is as a forum to develop children's understanding activities.In this case the formation of improving children's understanding is TPA Assistance, the priority of the program is teaching Tajweed, the ability to read the Qur'an.